Theology and the Boundary Discourse of Human Rights. - Regan, Ethna (Georgetown University Press, 2010)
What are human rights? Can theology acknowledge human rights discourse? Is theological engagement with human rights justified? What place should this discourse occupy within ethics? Ethna Regan seeks to answer these questions about human rights, Christian theology, and philosophical ethics. The main purpose of this book is to justify and explore theological engagement with human rights. Regan illustrates how that engagement is both ecumenical and diverse, citing the emerging engagement with human rights discourse by evangelical theologians in response to the War on Terror. The book examines where the themes and concerns of key modern theologiansùKarl Rahner, J. B. Metz, Jon Sobrino, and Ignacio Ellacur?aùconverge with the themes and concerns of those committed to the advancement of human rights. Regan also critically engages with the ôdisdainö for rights discourse that is found in the postliberal critiques of John Milbank and Stanley Hauerwas. This interdisciplinary volume will be of interest to students and scholars in the fields of systematic theology, theological ethics, human rights, religion and politics, and political theory.